Health communication patterns of clean and healthy behavior in islamic Boarding School - Uud Wahyudin; Kismiyati El Karimah (Universitas Padjadjaran, 2021)
The information received by Santries from various sources regarding infectious diseases in Pondok Pesantren’s environment is still confusing, which causes the Santries to be confused about finding reliable sources of information for their own health. They have sought this information through various sources. The purpose of this study is to determine who is the primary source of dissemination of health communication information related to Clean and Healthy Behavior and the health communication process within the Islamic boarding school in Sukabumi Regency, West Java, Indonesia. This study used a qualitative research method; then, the final results presented the health communication pattern among Islamic Boarding School in Sukabumi Regency. A case study approach was used in this study. The unavailability of updated, relevant data shows that the Central Government is still not actively moving towards the success of the PHBS Program at the national level in general and the education level of Islamic boarding schools in general. The difference between the provisions of the central government and the teachings of the Islamic religion that is applied in the Islamic Boarding School environment is one of the obstacles to implementing PHBS at the education level. The health information available in the mass media cannot be used by Santries to obtain information related to health. This research concludes that health information from Kyai’s teachings are the primary sources of health information in the Pesantren environment, supported by health information written in the Al- Quran and Al-Hadiths. Santries can receive health information outside the Pesantren environment through medical personnel, mass media, and information from the school. Suggestions from this research are PHBS counseling for Kyai and Santries according to national health standards under the guidance and supervision of the Ministry of Health.